Extra skeletal Ewing’s sarcoma in the parapharyngeal space: a rare case report - Talha Abbas; Nadir, Muhammad Asfandyar; Ur Rehman, Armaghan; Malik, Irshad; Wahab, Muhammad Umair; Masood, Maham (Journal of the Pakistan Medical Association, 2025)
Ewing’s sarcoma (ES) is a tumour commonly seen in children and usually affects the long bones. Its presence in the soft tissues of the parapharyngeal space is exceptionally rare, with only 29 cases reported in the literature so far. We report the case of a 21-year-old male with Extra skeletal Ewing’s Sarcoma (EES) in the parapharyngeal space, who presented with complaints of dysphagia and submandibular swelling displacing the tonsil and uvula. Despite normal systemic examinations, initial Fine Needle Aspiration Cytology (FNAC) suggested a benign cystic lesion, probably a pleomorphic adenoma. However, an excisional biopsy revealed malignant sheets of cells consistent with ES, confirmed by immunohistochemistry (IHC), showing NKX2.2 positivity which is a specific marker for ES. This case, being the first reported from Pakistan, emphasises the diagnostic challenge posed by rare presentations of EES in unusual locations and highlights the critical role of biopsy for accurate diagnosis. Keywords: Ewing’s Sarcoma, Parapharyngeal space, Head and Neck Neoplasm.